Jakarta Creative Tourism Travel Agent: Virtual Tour During Pandemic Covid-19 - Suheryadi, Heru; Andy Noviadi; FX Setiyo Wibowo; Fadia Azzahra (International Journal of Travel, Hospitality and Events, 2023)
Purpose: The aim of this research is to explore the virtual tours (VT) are provided by Jakarta Creative Tourism Travel Agents (JCTTA) for tourists to travel during the Covid-19 pandemic. Research methods: The research method used in this study is descriptive qualitative. Data collection was carried out by interview with key informants consisting of virtual tour service managers, visitors as service users. Data analysis was carried out descriptive qualitative form the results of interview which were used to answer problem formulations related to virtual tour products managed by JCCTA. Result and discussion: The results of this study indicate that VT has become an alternative in the tourism business and a viable option for travelers  during  the COVID-19 pandemic. VT enable travelers to explore tourist destinations without physically traveling, providing visual and interactive experiences through video and Google Earth. The discussion in this research highlights the advantages of VT as a means to sustain the tourism industry and offer a safe option for travelers during the pandemic. Implication: The implications suggest that 1) handling quickly in response to tourist complaints, especially network connections; 2) displays complete tourist attractions found in tourism destinations, so that no tourist attraction is overlooked; 3) presenting more attractive displays on the web site to attract new customers and consumers; 4) improve the quality of software and hardware used to produce VT packages; 5) Managers must try to establish a program for how this virtual tour business can still run  in  the  normal  era  after  the  COVID-19  pandemic  by  conducting  surveys  of previous customer interests. On the other hand, JCTTA's investment in software and hardware to produce virtual tour packages continues to generate profits for the company.   Keywords: virtual tour, covid-19 pandemic, travel agent